Limitations of the TheraMon®‐microsensor in monitoring occlusion therapy. (27th June 2016) - Schramm, Charlotte; Abaza, Annegret; Blumenstock, Gunnar; Bechtold, Till E.; Rickmann, Annekatrin; Bartz‐Schmidt, Karl‐Ulrich; Besch, Dorothea; Januschowski, Kai
Abstract: Purpose: A proof of principle study showed that the TheraMon ® ‐microsensor can reliably measure wearing times of glasses and occlusion patches while having no discomfort for the bearer. The goal of this study was to identify specific temperature profiles in a larger patient group wearing the microsensor with an occlusion patch on the eye, the forehead or in the trouser pocket. Methods: Temperature measurements with microsensors were performed at the orbital rim of the eye, at the forehead and in a trousers pocket of 20 healthy adults. The temperature measurements were analysed comparing the three locations using a repeated‐measuresanova with a 0.050 two‐sided significance level. Results: There was no significant temperature difference in wearing the microsensors at the orbital rim compared to forehead (p = 0.507). A significant difference could be detected if the microsensors had been in trousers pockets as compared to being positioned at orbital rim/forehead (p = 0.001). The study participants reported easy handling and comfortable wearing. Conclusion: This study demonstrates for the first time that TheraMon ® ‐microsensors are fully operational in monitoring occlusion therapy in a larger group of patients (20 adult study participants). Because of the microsensor's ease of handling further studies in a larger group of children is recommended.